In Vivo Assessment of Exercise-Induced Glenohumeral Cartilage Strain. Issue 7 (12th July 2018) - Zhang, Hanci; Heckelman, Lauren N.; Spritzer, Charles E.; Owusu-Akyaw, Kwadwo A.; Martin, John T.; Taylor, Dean C.; Moorman, C.T.; Garrigues, Grant E.; DeFrate, Louis E.
Background: The human shoulder joint is the most mobile joint in the body. While in vivo shoulder kinematics under minimally loaded conditions have been studied, it is unclear how glenohumeral cartilage responds to high-demand loaded exercise. Hypothesis: A high-demand upper extremity exercise, push-ups, will induce compressive strain in the glenohumeral articular cartilage, which can be measured with validated magnetic resonance imaging (MRI)–based techniques. Study Design: Descriptive laboratory study. Methods: High-resolution MRI was used to measure in vivo glenohumeral cartilage thickness before and after exercise among 8 study participants with no history of upper extremity injury or disease. Manual MRI segmentation and 3-dimensional modeling techniques were used to generate pre- and postexercise thickness maps of the humeral head and glenoid cartilage. Strain was calculated as the difference between pre- and postexercise cartilage thickness, normalized to the pre-exercise cartilage thickness. Results: Significant compressive cartilage strains of 17% ± 6% and 15% ± 7% (mean ± 95% CI) were detected in the humeral head and glenoid cartilage, respectively. The anterior region of the glenoid cartilage experienced a significantly higher mean strain (19% ± 6%) than the posterior region of the glenoid cartilage (12% ± 8%). No significant regional differences in postexercise humeral head cartilage strain were observed. Conclusion: Push-ups induce compressive strain on the glenohumeral joint articular cartilage, particularly at the anterior glenoid. This MRI-based methodology can be applied to further the understanding of chondral changes in the shoulder under high-demand loading conditions. Clinical Relevance: These results improve the understanding of healthy glenohumeral cartilage mechanics in response to loaded upper extremity exercise. In the future, these methods can be applied to identify which activities induce high glenohumeral cartilage strains and deviations from normal shoulder function.